Formal Hepatitis C Education Increases Willingness to Receive Therapy in an On-site Shelter-Based HCV Model of Care in Persons Experiencing Homelessness. (1st March 2022) - Partida, Diana; Powell, Jesse; Ricco, Margaret; Naugle, Jessica; Magee, Catherine; Zevin, Barry; Masson, Carmen L; Konadu Fokuo, J; Gonzalez, Daniel; Khalili, Mandana
Abstract: Background: The objective of this study was to evaluate the effectiveness of formal hepatitis C virus (HCV) education on engagement in therapy in persons experiencing homelessness in an on-site shelter-based model of care. As policies to eliminate Medicaid access restrictions to HCV treatment are expanded, patient education is paramount to achieving HCV elimination targets in difficult-to-engage populations including persons experiencing homelessness. Methods: This prospective study was conducted at 4 shelters in San Francisco and Minneapolis from August 2018 to January 2021. Of the 162 HCV Ab–positive participants, 150 participated in a 30-minute HCV education session. Posteducation changes in knowledge, beliefs, barriers to care, and willingness to accept therapy scores were assessed. Results: Following education, knowledge scores (mean change, 4.4 ± 4.4; P < .001) and willingness to accept therapy (70% to 86%; P = .0002) increased. Perceived barriers to HCV care decreased (mean change, –0.8 ± 5.2; P = .001). Higher baseline knowledge was associated with lesser gain in knowledge following education (coef., –0.7; P < .001). Posteducation knowledge (odds ratio, 1.2; P = .008) was associated with willingness to accept therapy. Conclusions: An HCV educational intervention successfully increased willingness to engage in HCV therapy in persons experiencing homelessness in an on-site shelter-based HCV model of care.